MAKNA HIDUP REMAJA PEREMPUAN YANG PERNAH MENGALAMI ABORSI - Berliana Agustinne; Aditama Pramono Jati; Muhammad Rivaldy; Untung Subroto (STKIP Subang, 2025)
Abortion in adolescent girls is a complex phenomenon that affects various aspects of life, including psychological and existential aspects. This study aims to explore the meaning of life of adolescent girls who have experienced abortion, using a phenomenological qualitative approach. The research subjects consisted of six adolescent girls who were selected through purposive sampling technique. Data were collected through in-depth interviews, observation, and reflective documentation, then analysed using a phenomenological thematic approach. The results showed that the abortion experience became a turning point in the participants' lives, prompting deep reflection on identity, social relationships, and life values. The majority of participants experienced emotional struggles such as guilt, regret, and alienation, but gradually found new meanings that were personal, spiritual, and social. This process demonstrated post-traumatic growth, with participants able to reconstruct life goals and rebuild self-esteem. This study highlights the importance of empathic psychological support, meaning-based counselling, and culturally and religiously sensitive approaches in assisting post-abortive adolescents.